Securing continuation of treatment for children with cancer in times of social unrest and pandemic. Issue 6 (31st May 2021) - Zuleta, Verónica; Berliner, Josefina; Rossell, Nuria; Zubieta, Marcela
Abstract: Background: Childhood cancer in Chile reports 500 new cases each year of which 85% are treated in the public health system. Governmental programs ensure access to diagnosis, treatment, follow up and palliative care, whereas Fundación Nuestros Hijos (FNH) provides supportive care for non‐covered medical and psychosocial needs. Common financial difficulties in families of children and adolescents with cancer increased considerably when a wave of social unrest arose in October 2019 and the Covid‐19 pandemic in March 2020 hit the country, leaving families of children with cancer facing greater challenges. Aims: We report here the support activities and interventions carried out by FNH to help the families during the crisis of these months. Methods: A socioeconomic survey was conducted among FNH's beneficiary families to know their needs. During these months of acute crisis for many families, support activities and interventions were developed and varied types of aid were allocated to help the families. Results: The main results of the survey in which 525 (70%) of FNH's beneficiary families participated showed that 75% of them had only one breadwinner, and 52% had one unemployed family member. Almost 90% of job loss happened during the months of social unrest and pandemic. Four main interventions: (a) safe transportation, (b) food, (c) heating, (d) internet connectivity, were organized to support important needs of the families and prevent children to miss treatment appointments. Additionally, some families who did not access governmental emergency aid were guided in the process. Conclusions: The aid provided helped the families to relieve some of their needs, facilitated the continuation of treatment during the pandemic, and made the caregivers feel supported and listened.